FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN DI KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR - Enil, Yuliana; Djou, Laurentius Dominicus Gadi (Jurnal Riset Ilmu Akuntansi, 2022)
This study aims to determine what are the factors that influence the income of fishermen in Borong District, East Manggarai Regency. This type of research is quantitative research using hypothesis testing, with data collection techniques (1) observation, (2) questionnaires, (3) interviews, (4) documentation and (5) literature study. Data analysis techniques using the SPSS data processing formula using descriptive statistical formulas, instrument tests, classical assumption tests, multiple linear regression tests and hypothesis testing. The results of the study show that: (1) the first hypothesis is that capital influences and is significant on the income of fishermen in Borong District, East Manggarai Regency. This is evidenced by the coefficient value of the capital variable of 0.168 with tcount> ttable (2.737> 1.987) and a significant level of 0.008 <0.05. (2) the second hypothesis is that labor has an influence and is significant on the income of fishermen in Borong District, East Manggarai Regency. This is evidenced by the coefficient value of the labor variable of 0.189 with tcount> ttable (3.192> 1.987) and a significant level of 0.002 <0.05. (3) the third hypothesis is that experience influences and is significant on the income of fishermen in Borong District, East Manggarai Regency. This is evidenced by the experience variable coefficient value of 0.435 with tcount> ttable (4.986> 1.987) and a significant level of 0.000 <0.05.